Comparison of In Vitro Testing Antifungal Activity between Rosemary Essentials Oil and Fluconazol on Candida species Isolate from HIV/AIDS Patients with Candidiasis Oral - Putri Intan Primasari; Dwi Murtiastutik; Pepy Dwi Endraswari; Cita Rosita Sigit Prakoeswa; Evy Ervianti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: The most common opportunistic infection obtained in patients with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) is Oral Candidiasis (OC). Currently widely reported about increased fluconazole resistance, as a therapy that is often used in patients with HIV/AIDS with OC. For this reason, effective antifungal agents are needed as alternative therapies. Several studies have reported some antifungal activity from rosemary essential oils. Purpose: The aim of this study is to evaluate the antifungal activity between rosemary essential oils and fluconazole against the isolates used by Candida sp. taken from HIV / AIDS patients with OC. Methods: This research was an experimental laboratory study with a post-test only design of 40 Candida sp. isolates from HIV / AIDS patients with OC in the Outpatient Unit and Inpatient Installation of the Infectious Disease Intermediate Care Unit (UPIPI) Dr. Soetomo General Academic Teaching Hospital, Surabaya. Examination of antifungal activity using conventional test methods with disk diffusion. Result: Disk diffusion test result revealed average inhibition zone of rosemary essential oil in Candida albicans 1,75±3,64 mm and Candida non-albicans 1,5±3,08 mm, while the average inhibition zone of fluconazole in Candida albicans 17,9±8,62 mm and Candida non-albicans 4,85±7,9 mm. There was significant difference (p <0.001) between the inhibition zone formed in Candida albicans by fluconazole and rosemary essential oil, but no significant difference of inhibition zone formed in Candida non-albicans. Conclusion: Antifungal activity fluconazole has greater than Rosemary essential oils in Candida albicans.